Evaluation of allometric equations of aboveground biomass in a semideciduous tropical forest of Yucatan - Ramírez Ramírez, Gustavo; Dupuy Rada, Juan Manuel; Ramírez y Avilés, Luis; Solorio Sánchez, Francisco Javier (Instituto de Ecología, A.C., 2017)
The objectives of this study were to develop and compare allometric equations of aboveground biomass (AGB) for a semi-deciduous tropical forest of the ejido (system of communal or cooperative farming) San Agustin, Yucatan, Mexico, and to compare them to existing equations. Forty seven trees of 18 different species with diameters between 2.5 cm and 41.5 cm were selected. The diameter of each tree was measured before felling, and the height was estimated before and measured after felling. Fresh weight of each component (stem, branches, leaves) was measured in the field, and samples were taken to determine dry weight in the laboratory and to extrapolate to the whole individual. Six allometric equations with different functional forms were explored, and tested using the Akaike information criterion (AIC), adjusted R2value and cross validation. The best equation yielded an AIC value of 48.36 and an adjusted R2 of 0.96. Cross-validation showed an adjusted R2 value of 0.72 and a coefficient of agreement of 0.56. Unexpectedly, this equation is less precise than others used in the forests of the Yucatan Peninsula, including equations developed locally and in other continents, with very contrasting sample sizes. However, the best equation obtained in this study allows adequate estimates of AGB of the semideciduous tropical forests of Yucatan, especially for the largest trees, which are the most influential.